Mapping early childhood phonological abilities in PAUD Tasikmalaya: A qualitative descriptive study - Pratiwi, Anggia Suci; Wijana, I Dewa Putu; Sutrisno, Adi; Nurhayati, Endang; Nurdin, Rahil Rohimah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2025)
This study maps the phonological abilities of early childhood in PAUD Tasikmalaya, focusing on language sound acquisition and use. Using a descriptive qualitative method, data were collected through classroom observations and interviews with 4- to 6-year-old students in various PAUD institutions, including state-owned, private, Islamic, and Christian schools across Tasikmalaya. The study involved 315 children from RA Baiturrahman, TK Negeri Pembina, TK Cangkurileung, TK IT Ihya As-Sunah, and Joykids.Speech data were analyzed through reduction, display, and verification, ensuring validity through expert judgment. Findings reveal that vowel mastery progresses with age. At four years old, children fully master initial and final position vowels [a, i, u, e, o] but struggle with middle-position vowels. By five years, they improve in middle-position vowels but still face challenges. Six-year-olds fully master vowels except for some middle-position difficulties.Consonant acquisition also develops over time. Four-year-olds master consonants [c, g, j, f, w, y]. Five-year-olds expand to [c, g, j, k, t, f, b, w, y]. Six-year-olds achieve broader mastery, including [c, g, j, d, k, t, f, s, x, z, b, p, w, m, n, y]. The study highlights a structured progression in phonological development among early childhood learners.